Pelatihan Program Maharah Al - ‘arabiyyah dengan Creative Learning Strategies Berbasis Educational Games: Studi Kasus di Madrasah Aliyah Swasta Terpadu Permata Umat Trenggalek - Naja Alwi Mawardy; Purwanto Purwanto; Nedya Varchaty (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
This community service program aims to improve Arabic language skills through creative learning strategies based on educational games designed for the learning aspects of maharah istima', kalam, qira'ah, kitabah, and qawa'id learning. Mastery of maharah al-'arabiyah at the Madrasah Aliyah level still faces various obstacles. Mainly low learning motivation, lack of method variation, and dominated by textual learning approaches. This activity was carried out at the Madrasah Aliyah Swasta Terpadu Permata Umat, Trenggalek using qualitative methods through observation, interviews, direct mentoring, and documentation of student activities during the training process. The results of this community service program show that the implementation of educational games such as matching games, interactive dialogues, istima' habits, kitabah habits, roleplay games, guessing games, and grammar materials (nahwu and sharaf) combined with a reward system can foster and increase active participation, courage to speak, and increase student motivation in learning Arabic. This activity emphasizes that educational games are an effective approach in improving Arabic language competency in the madrasah environment.